Choosing the right instrument: Environmental policy in the presence of a double dividend - Ronnie Schöb (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1995)
This paper analyses second-best optimal environmental policies in the presence of a double dividend. Using a partial equilibrium model, the paper first reconfirms the well-known result that the existence of a double dividend (in its weak form) favours environmental policy instruments which - yielding the same improvement in environmental quality - maximise its tax revenues. Additional revenues can be used to reduce the distortion of the rest of the tax system. Without uncertainty, environmental taxes and auctioned permit schemes are equally appropriate. In the presence of uncertainty, however, the efficient choice of taxes or permits depends on the relative magnitudes of the marginal environmental damages and the marginal benefits from consuming a polluting good. In the second part, the paper, therefore, analyses the effect of a double dividend on the optimal choice of instruments in the presence of uncertainty. It shows that, although the revenue capacity effect generates additional welfare effects, the first-best choice rule between price and quantity regulation (Weitzman 1974) remains valid in a world with distortionary taxation.
Keywords: H23; Q28; 330; Umweltabgabe; Emissionshandel; Externer Effekt; Risiko; Wohlfahrtsanalyse; Theorie